2017
DOI: 10.1038/ncomms14484
|View full text |Cite
|
Sign up to set email alerts
|

Drebrin-mediated microtubule–actomyosin coupling steers cerebellar granule neuron nucleokinesis and migration pathway selection

Abstract: Neuronal migration from a germinal zone to a final laminar position is essential for the morphogenesis of neuronal circuits. While it is hypothesized that microtubule–actomyosin crosstalk is required for a neuron's ‘two-stroke' nucleokinesis cycle, the molecular mechanisms controlling such crosstalk are not defined. By using the drebrin microtubule–actin crosslinking protein as an entry point into the cerebellar granule neuron system in combination with super-resolution microscopy, we investigate how these cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
55
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 70 publications
2
55
0
Order By: Relevance
“…FLPs were observed not only in the V‐SVZ‐derived new neurons (Fig ) but also in other migrating neurons generated in the embryonic ganglionic eminences (Appendix Fig S2). All of these neurons extend a long leading process, in which proximal‐region cytoskeletal changes drive somal translocation (Shinohara et al , ; Yang et al , ; Nishimura et al , ; Ota et al , ; Trivedi et al , ), and distal‐region cytoskeletal changes determine directionality (Martini et al , ; Lysko et al , , ). Since FLPs can develop into lateral dendrites after neuronal migration termination (Appendix Fig S1C and D), the mechanism for FLP formation, which is controlled by Sema3E‐PlexinD1 signaling, could regulate migration termination and the initiation of differentiation, simultaneously and rapidly, providing an efficient strategy for neuronal development.…”
Section: Discussionmentioning
confidence: 99%
“…FLPs were observed not only in the V‐SVZ‐derived new neurons (Fig ) but also in other migrating neurons generated in the embryonic ganglionic eminences (Appendix Fig S2). All of these neurons extend a long leading process, in which proximal‐region cytoskeletal changes drive somal translocation (Shinohara et al , ; Yang et al , ; Nishimura et al , ; Ota et al , ; Trivedi et al , ), and distal‐region cytoskeletal changes determine directionality (Martini et al , ; Lysko et al , , ). Since FLPs can develop into lateral dendrites after neuronal migration termination (Appendix Fig S1C and D), the mechanism for FLP formation, which is controlled by Sema3E‐PlexinD1 signaling, could regulate migration termination and the initiation of differentiation, simultaneously and rapidly, providing an efficient strategy for neuronal development.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the migratory direction of neuroblasts was abnormal in the OB of DXKO mice. These results are consistent with the recent study that drebrin is required for microtubule–actomyosin coupling and steers the direction of centrosome and somal migration, as well as the switch from tangential to radial migration (Trivedi et al ., ). Tangential migration is a chain migration that involves close contact of the neuroblasts with each other (Lois & Alvarez‐Buylla, ; Wichterle et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…The Siah2 E3 ubiquitin ligase appears to act as a central regulator of GZ occupancy by modulating two distinct cell biological processes. Previous results have shown that Siah2 restrains radial migration in progenitors by tagging for ubiquitin-proteasome degradation targets that are required for the pro-migratory adhesive interactions and actin-microtubule crosslinking that are essential for GZ exit and migration along glial fibers (Famulski et al, 2010;Trivedi et al, 2017) . The current study has extended these findings to implicate Siah2 as an active participant in GZ occupancy by supporting primary cilium maintenance in GNPs: Siah2 targets Pard3 and Pifo for degradation, thereby ensuring the reception of signals from the Shh morphogen that promote GNP proliferation at the expense of CGN differentiation.…”
Section: Discussionmentioning
confidence: 99%